Pengembangan Video Berbasis Animasi Powtoon untuk Materi Komponen Ekosistem IPA untuk Siswa Sekolah Dasar - Jumaidil Khair; Lagiono; Yudha Adrian; M. Saufi; Abidinsyah (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Most of the teachers have not been able to take advantage of the learning support facilities that are already available in each class in the form of projectors, besides that, from within learning which discusses the components of the ecosystem, when delivering material the teacher only uses printed media in the form of books. The advantage of this learning media is that videos can be played repeatedly, the learning process becomes clearer and more interesting. The purpose of developing this learning media is how the feasibility of learning media using Powtoon-based animated videos is. How is the practicality of learning media using Powtoon-based animated videos, how is the attractiveness of learning media using Powtoon-based animated videos. The model used is ADDIE (1990) 1. Analysis (analysis), 2. Design (design), 3. Development (development), 4. Implementation (apply), 5. Evaluation (feedback). The subjects in the study were expert validators and users. The research was conducted offline. The types of data obtained in this research and development are quantitative data and qualitative data. Quantitative data was obtained from the results of the calculation of the validation sheet and questionnaire and qualitative data was obtained from comments and suggestions from the research subjects. The results showed that in the development of learning video media in science subjects, more precisely on the Ecosystem Component material, the validity of the material expert was 80% (valid), the media expert was 80% (valid), and the teacher's assessment was 92% (very practical). 82% students (very interesting).